The Jamaica asthma and allergies national prevalence survey: rationale and methods - Kahwa, Eulalia K; Younger, Novie O; Wint, Yvonne B; Waldron, Norman K; Hewitt, Hermi H; Knight-Madden, Jennifer M; Bailey, Kay A; Edwards, Nancy C; Talabere, Laurel R; Lewis-Bell, Karen N (Université d'Ottawa | University of Ottawa, 2010)
Abstract Background Asthma is a significant public health problem in the Caribbean. Prevalence surveys using standardized measures of asthma provide valid prevalence estimates to facilitate regional and international comparisons and monitoring of trends. This paper describes methods used in the Jamaica Asthma and Allergies National Prevalence Survey, challenges associated with this survey and strategies used to overcome these challenges. Methods/Design An island wide, cross-sectional, community-based survey of asthma, asthma symptoms and allergies was done among adults and children using the European Community Respiratory Health Survey Questionnaire for adults and the International Study of Asthma and Allergies in Children. Stratified multi-stage cluster sampling was used to select 2, 163 adults aged 18 years and older and 2, 017 children aged 2-17 years for the survey. The Kish selection table was used to select one adult and one child per household. Data analysis accounted for sampling design and prevalence estimates were weighted to produce national estimates. Discussion The Jamaica Asthma and Allergies National Prevalence Survey is the first population- based survey in the Caribbean to determine the prevalence of asthma and allergies both in adults and children using standardized methods. With response rates exceeding 80% in both groups, this approach facilitated cost-effective gathering of high quality asthma prevalence data that will facilitate international and regional comparison and monitoring of asthma prevalence trends. Another unique feature of this study was the partnership with the Ministry of Health in Jamaica, which ensured the collection of data relevant for decision-making to facilitate the uptake of research evidence. The findings of this study will provide important data on the burden of asthma and allergies in Jamaica and contribute to evidence-informed planning of comprehensive asthma management and education programs.